The effect of experimental educational exercises to develop and measure some physical abilities and shooting accuracy from high jumping for young handball players - Azeez Salman, Hardan; Youssuf Abdulzahra, Yaqub; Ghazi Azeez Salman, Haider (International Journal of Psychosocial Rehabilitation, 2020)
Introduction to the research and its importance: The researchers discussed the importance of using modern training methods in training and special exercises and their effectiveness in developing physical abilities, which in turn reflected positively on developing accuracy of correction, which is one of the basics on which correction skills in the game of handball are built.Research problem: During the researchers' observation that they are coaches and former players of the handball game, and through field follow-up to the Youth League, he noticed that there is fluctuation in the technical performance of the accuracy of correction for these players, represented by the lack of use of special exercises, which enables them to do their best in training and competitions, so the researchers decided to study This problem is through preparing special exercises for some physical abilities and knowing their impact on the performance of accurate correction from high jumping for young handball players.Research objectives: Preparing special exercises for the development of some physical abilities and accuracy of correction from high jumping for young handball players.Identify the differences between the pre and post tests of the research sample, according to the effect of special exercises on some physical abilities and the accuracy of correction from high jumping for young handball players.The two research hypotheses: The special exercises used have a positive effect on the development of some physical abilities and the accuracy of shooting from high jumping for youth handball players. 2. There are statistically significant differences between the pre- and post-tests of the research sample due to the effect of special exercises on some physical abilities and the accuracy of shooting from high jumping for young handball players and in favor of the post tests.Fields of research: The human field: the players of the Army Club for the youth category of ages (17-19) years, the temporal domain: from 12/10/2019 to 4/20/2020, the spatial field: the closed hall of the Wissam Al Majd Sports Club.Chapter Three: This chapter included a presentation of the results of statistical treatment using a set of tables, then analyzing and discussing them in an accurate scientific manner and supported by scientific sources through this discussion, then reaching the research objectives and verifying the research hypothesis.Chapter Four: The conclusion included conclusions, including (the organization of the performance and application of special exercises according to the curriculum prepared by the researcher for the research sample contributed to raising the level of performance of some physical abilities and the accuracy of correction from jumping high with the handball and this was shown through the dimensional results) and recommendations from them (necessity) Interest in the correction skill from high jumping, as it is one of the most important and difficult offensive skills, as well as it leaves more compatibility for the player by increasing accuracy during correction)